2017
DOI: 10.1055/s-0036-1597548
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Secondary Hydrocephalus after Excision of Huge Encephaloceles in Neonates: Case Study

Abstract: Early surgical excision provides effective treatment of huge encephaloceles. Overall, 21% of cases require cerebrospinal fluid (CSF) diversion afterward depending on associated anomalies. Despite their size, giant encephaloceles can have an excellent prognosis with no need for further treatment or CSF diversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
6
1
4
Order By: Relevance
“…La prevalencia del encefalocele varía de 0.08 a 0.4 por cada 1 000 nacidos vivos [4][5][6].El meningohidroencefalocele es un defecto congénito del tubo neural cuya característica es una herniación o protrusión de las meninges, encéfalo y ventrículos a través de un defecto del cráneo; este saco herniario esta generalmente cubierto por cuero cabelludo [1][2][3][4][5]. La herniación ocurre entre las 8 a 12 semanas de gestación en el sitio de una disrupción mesenquimatosa local, se origina por la separación anormal entre el ectodermo de superficie y el neural en los sitios de cierre [4]. Aproximadamente el 75% de los encefaloceles están ubicados en la región occipital, seguido de la frontoetmoidal (13% -15%) y parietal (10% -12%) [6].…”
Section: Discussionunclassified
See 3 more Smart Citations
“…La prevalencia del encefalocele varía de 0.08 a 0.4 por cada 1 000 nacidos vivos [4][5][6].El meningohidroencefalocele es un defecto congénito del tubo neural cuya característica es una herniación o protrusión de las meninges, encéfalo y ventrículos a través de un defecto del cráneo; este saco herniario esta generalmente cubierto por cuero cabelludo [1][2][3][4][5]. La herniación ocurre entre las 8 a 12 semanas de gestación en el sitio de una disrupción mesenquimatosa local, se origina por la separación anormal entre el ectodermo de superficie y el neural en los sitios de cierre [4]. Aproximadamente el 75% de los encefaloceles están ubicados en la región occipital, seguido de la frontoetmoidal (13% -15%) y parietal (10% -12%) [6].…”
Section: Discussionunclassified
“…La ecografía continúa siendo de gran valor en el diagnóstico prenatal, permite evidenciar la presencia o ausencia de tejido cerebral en el defecto; además a través del estudio exhaustivo, permite evaluar de forma integral el desarrollo fetal y la presencia de otras alteraciones del neuro-eje [4][5][6][7]. Clínicamente, las encefaloceles gigantes son evidentes debido a su morfología [8].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…16 Other authors have also suggested that the larger the EC sac size, the greater will be the likelihood of hydrocephalus development. 17,18 Predicting the likelihood of hydrocephalus development and the associated risk factors in patients with EC can help physicians tailor their treatment strategies to ensure lower mortality and morbidity rates in affected patients. In this study, we reviewed our series of patients with EC and analyzed the risk factors/predictors that correlate with the occurrence of hydrocephalus.…”
mentioning
confidence: 99%